2019
DOI: 10.1007/s13201-019-0926-8
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals by chitin: equilibrium, kinetic and thermodynamic studies

Abstract: Adsorption is one of the most commonly used methods for the wastewaters treatment. In this work, we studied the impact of experimental conditions on the adsorption of heavy metals M(II) (M = Cd, Ni, Cu, Pb and Zn) in batch system using chitin obtained from crab shells. This biomaterial is selected because of its low cost, availability and efficiency. The M(II) adsorption was found to be dependent on the initial pH, contact time, initial concentration of M(II) and biomass dose. The kinetic models of Elovich, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 55 publications
8
61
0
Order By: Relevance
“…A biomass of 2-5 g/L of chitin was found to be optimal for maximum divalent metal ion removal [53], and our experimental conditions of 4 g/L are consistent with these values. The adsorption of metals to chitin is very fast, and it has been shown that full equilibrium is already reached after 30 min [53], and in some cases there is evidence that 10 minutes are enough for chitin-adsorption equilibrium except for a few elements, like Fe [35,48]. Our experimental time of 60 min was thus enough to warrant full adsorption equilibrium with metal ions in the treatment solutions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A biomass of 2-5 g/L of chitin was found to be optimal for maximum divalent metal ion removal [53], and our experimental conditions of 4 g/L are consistent with these values. The adsorption of metals to chitin is very fast, and it has been shown that full equilibrium is already reached after 30 min [53], and in some cases there is evidence that 10 minutes are enough for chitin-adsorption equilibrium except for a few elements, like Fe [35,48]. Our experimental time of 60 min was thus enough to warrant full adsorption equilibrium with metal ions in the treatment solutions.…”
Section: Discussionsupporting
confidence: 83%
“…Metal uptake by chitin and chitosan is reported as determined by adsorption processes [30], with adsorption depending on several factors such as chitin/chitosan biomass and exposure time [31]. A biomass of 2-5 g/L of chitin was found to be optimal for maximum divalent metal ion removal [53], and our experimental conditions of 4 g/L are consistent with these values. The adsorption of metals to chitin is very fast, and it has been shown that full equilibrium is already reached after 30 min [53], and in some cases there is evidence that 10 minutes are enough for chitin-adsorption equilibrium except for a few elements, like Fe [35,48].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For instance, chitin obtained from H. illucens has been used as a sorbent of organic dye [ 30 ]. Chitin obtained from other sources is a good sorbent for heavy metals [ 31 , 32 , 33 ]. However, there is a lack of studies on the possibility of using chitin from H. illucens in the sorption of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The laterite substrate was found more efficient for arsenic removal whereas limestone substrate in CWs exhibited greater elimination of Cd, Zn, Zn and Mn [71]. There were investigations on the sorption capacities, morphology properties and physicochemical characteristics of discarded mushroom-stick biochar (DMB) synthesized and negative free energy (∆G°) showed the endothermic and spontaneous adsorption [58]. Cr(III) can be adsorbed up to 97.48% by using fly ash (the solid waste from coal-fired power plants) modified with 20 wt% of KOH at 15-20ºC and a contact time of 120 min [59].…”
Section: Adsorption By Agriculture/plant/animal Wastesmentioning
confidence: 99%